HANR promotes lymphangiogenesis of hepatocellular carcinoma via secreting miR‐296 exosome and regulating EAG1/VEGFA signaling in HDLEC cells. Issue 10 (24th May 2019) - Shi, Yang; Yang, Xiaohua; Xue, Xiaofeng; Sun, Ding; Cai, Peng; Song, Qingwei; Zhang, Bin; Qin, Lei
Abstract: The long noncoding RNA HANR has been shown to be involved in the progression of hepatocellular carcinoma (HCC). However, the underlying mechanism of HCC‐associated long noncoding RNA (HANR)–regulated HCC metastasis and lymphangiogenesis has not been elucidated. RT‐qPCR and Western blot methods were utilized to detect the gene expressions. Interaction of HANR with miR‐296 was predicted by a bioinformatic program and validated by a dual‐luciferase reporter assay. For the functional experiment, a transwell invasion assay was utilized to examine the invasion abilities of HepG2 and Huh‐7 cells. The lymphatic vessel formation assay was used to show the HCC‐associated lymphatic vessel formation ability of human dermal lymphatic endothelial cells (HDLEC). HANR was shown to directly bind to miR‐296, and miR‐296 downregulated HANR expression in HepG2 cells. Then, we observed that miR‐296 inhibitor transfection in shHANR HCC cells could promote lymphatic vessel formation and invasion of HDLEC cells compared with shHANR HCC cells. EAG1 or VEGFA overexpression in HDLEC cells rescued lymphatic vessel formation and invasion in HDLEC cells coincubated with the medium of HepG2 cells expressing shHANR or miR‐296 mimic. Ultimately, HANR knockdown and miR‐296 mimic led to a significant decrease in the EAG1 and VEGFA expression levels in HepG2 cells. Here, we reveal a novel molecular mechanism in which the HANR/miR‐296/EAG1/VEGF axis is responsible for the lymphangiogenesis of HCC cells. Our findings provide more insights into developing therapeutical or diagnostic methods by targeting HANR. Abstract : In this study, we reveal a novel molecular mechanism in which the HANR/miR‐296/EAG1/VEGF axis is responsible for the lymphangiogenesis of hepatocellular carcinoma (HCC) cells. Our findings provide more insights into developing therapeutical strategies or diagnostic markers by targeting HCC‐associated long noncoding RNA.